Keanekaragaman Odonata di kawasan bendungan lempake, sungai karang mumus dan sungai berambai Samarinda - Ratri Arbia Nisita; Nova Hariani; Sus Trimurti (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
Knowledge of the diversity of dragonflies (Odonata) is very important for river management which is used for various purposes by humans. This research aims to determine the diversity of Odonata in the waters of Bendungan Lempake, Karang Mumus River and Berambai River Samarinda. Sampling was done by using purposive sampling technique through insect net with transect method along with the river flow, 5 times at each location for one month in the morning and evening. The samples obtained were prepared, stored on triangular paper containing camphor, and identified using entomological guidelines. Environmental temperature, humidity, and acidity of the water are calculated using standard measurement tools. Data is displayed in the form of the number of types and a description of each type. The results showed that 1025 individual dragonflies were found belonging to 22 species and 4 families of Odonata. The diversity index value (H') of dragonflies in the waters of the Bendungan Lempake is 2.83, the Karang Mumus River is 2.52 and the Berambai River is 2.53, which are classified as a medium category. The conclusion of this research is that the waters of Bendungan Lempake, Karang Mumus River, and Berambai River are still supporting as habitat for dragonflies to live and breed.